Majorant estimates for solutions of quadratic difference systems with lag - Davydov, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
Systems of differential equations with lag with quadratic right-hand sides are considered. A compact matrix form for representing these systems in the general form is suggested. Upper and lower bounds for solutions of systems of quadratic differential equations with arbitrary lag are obtained by using quadratic Lyapunov functions.